1983
DOI: 10.1128/aac.23.6.932
|View full text |Cite
|
Sign up to set email alerts
|

Synergy of combinations of vancomycin, gentamicin, and rifampin against methicillin-resistant, coagulase-negative staphylococci

Abstract: The activity of combinations of vancomycin (2 or 10 ,ug/ml), gentamicin (0.3 ,ug/ ml), and rifampin (0.03 [xg/ml) against methicillin-resistant, coagulase-negative staphylococcal isolates was determined by the time-kill method. Combinations of rifampin with gentamicin or with vancomycin 2 ,ug/ml demonstrated enhanced killing against 13 of 17 and 13 of 25 strains, respectively. However, rifampinresistant strains were selected with the latter combination in the remaining 12 of 25 studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Our study and others (1,2,5,10,23,29,32,39,43,47,49,51,53) have indicated that vancomycin and rifampin are consistently active against both oxacillin-susceptible and -resistant staphylococci. The clinical efficacy of vancomycin has been established for both heteroresistant S. aureus (8) and S. epidermidis (23,52).…”
Section: Discussionmentioning
confidence: 99%
“…Our study and others (1,2,5,10,23,29,32,39,43,47,49,51,53) have indicated that vancomycin and rifampin are consistently active against both oxacillin-susceptible and -resistant staphylococci. The clinical efficacy of vancomycin has been established for both heteroresistant S. aureus (8) and S. epidermidis (23,52).…”
Section: Discussionmentioning
confidence: 99%
“…For example, vancomycin penetration into lung tissue is not sustained, and the same was seen for the meninges and infected bone, whereas rifampin easily penetrates these tissues (61,109,120). The rifampin-vancomycin in vitro interaction appears to range from antagonistic to indifferent, with very few synergistic studies (25,26,112,119,158,218,246,251,258,261). Tuazon et al showed that the rifampin-vancomycin combination had "partial synergism" with only 25% of the MSSA isolates, with the remainder being indifferent, while the nafcillin-rifampin combination had "partial synergism" for 60% of the isolates (246).…”
Section: Staphylococcimentioning
confidence: 99%
“…In vitro (22,24, 33) and in vivo (23, 25, 33) studies with Staphylococcus aureus and Staphylococcus epidermidis in our laboratory, however, indicated that a second mechanism by which cell wall-active antibiotics (,-lactams, vancomycin) enhance the bactericidal effect of aminoglycosides (or rifampin) is by preventing regrowth of relatively resistant subpopulations. Twentyfour-hour time kill studies often do not distinguish between the aforementioned mechanisms of drug potentiation, and * Corresponding author.…”
mentioning
confidence: 95%